2018
DOI: 10.1177/2054358118799693
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 3-Year Survival in Patients Receiving Maintenance Dialysis: An External Validation of iChoose Kidney in Ontario, Canada

Abstract: Background:Many patients with end-stage kidney disease (ESKD) do not appreciate how their survival may differ if treated with a kidney transplant compared with dialysis. A risk calculator (iChoose Kidney) developed and validated in the United States provides individualized mortality estimates for different treatment options (dialysis vs living or deceased donor kidney transplantation). The calculator can be used with patients and families to help patients make more educated treatment decisions.Objective:To val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…A key barrier to ACD discussion is the limited ability for caregivers to accurately estimate prognosis. 13,14,24 We specifically examined characteristics associated with DNR status to identify emerging risk factors that may trigger ACD discussions. We identified 2 functional measures (inability or requiring aid for meal preparation, laundry) that were more common with a DNR order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key barrier to ACD discussion is the limited ability for caregivers to accurately estimate prognosis. 13,14,24 We specifically examined characteristics associated with DNR status to identify emerging risk factors that may trigger ACD discussions. We identified 2 functional measures (inability or requiring aid for meal preparation, laundry) that were more common with a DNR order.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to improve ACD planning include the lack of time required for a full discussion, concerns about invoking hopelessness in patients, lack of training for staff in ACD discussions, limited information on prognostication, and uncertainty when ACD discussions should occur. 11-14 To better improve EOL care for patients, we examined the interprovincial and within Ontario variation in DNR orders and identified clinical characteristics (demographic, comorbidities, and functionality) associated with a DNR order.…”
Section: Introductionmentioning
confidence: 99%
“…63 In a 2018 external validation of the app, including 22 520 patients on maintenance dialysis and 4505 kidney transplant recipients in Ontario, Canada, the adapted iChooseKidney tool had adequate predictive accuracy. 143 The app is being used in a multifaceted provincial quality initiative to improve access to KT and LDKT in Ontario. 144 A study tested a Web-based LT decision aid and found that it was feasible and improved knowledge among LT candidates.…”
Section: Electronic and Mobile Health Initiativesmentioning
confidence: 99%
“…Development of the resources and papers should include a critical literature review of published data on prognostic tools for survival of dialysis and conservative pathway patients. Useful resources include papers by Couchoud et al, 31 McArthur et al, 32 and Tan et al 33 Explanatory notes for Table 22, Conservative Kidney Management Project C4. A set of materials will be identified, collated, and assembled, including those identified in Project C3.…”
Section: Deliverablesmentioning
confidence: 99%